Lucio phenomenon and antiphospholipid antibodies in leprosy mimicking rheumatologic disorders: a case report - Rudy Hidayat; Johanda Damanik; Abirianty Priandani Araminta; Melani Marissa; Maria Angela Putri Maharani (Reumatismo)
Hansen’s disease, also known as leprosy, is often termed “the great imitator” due to its diverse clinical presentations that can mimic various rheumatologic disorders. We present the case of a 34-year-old female who developed extensive purpuric rashes, initially raising suspicion of vasculitis. Laboratory investigations revealed triple-positive antiphospholipid antibodies. However, skin smears and histopathological examination confirmed a diagnosis of diffuse lepromatous leprosy complicated by Lucio phenomenon. This case highlights the importance of considering infectious etiologies, such as leprosy, in the differential diagnosis of vasculitis and rheumatologic diseases. Given the overlapping clinical features, a comprehensive patient history and careful interpretation of autoantibody tests are essential for achieving an accurate diagnosis.